2019
DOI: 10.3390/mi10090594
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of Particles Using Inertial Focusing and Laminar Vortex Technology: A Review

Abstract: The capability of isolating and sorting specific types of cells is crucial in life science, particularly for the early diagnosis of lethal diseases and monitoring of medical treatments. Among all the micro-fluidics techniques for cell sorting, inertial focusing combined with the laminar vortex technology is a powerful method to isolate cells from flowing samples in an efficient manner. This label-free method does not require any external force to be applied, and allows high throughput and continuous sample sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 92 publications
0
32
0
Order By: Relevance
“…(2009), Chang et al. (2010) or Volpe, Gaudiuso & Ancona (2019), which may possibly be improved by controlling the size of the recirculation zones; (ii) microreactors such as the microcrystallizer described by (Rimez et al. 2019), which may also be improved by promoting passive mixing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009), Chang et al. (2010) or Volpe, Gaudiuso & Ancona (2019), which may possibly be improved by controlling the size of the recirculation zones; (ii) microreactors such as the microcrystallizer described by (Rimez et al. 2019), which may also be improved by promoting passive mixing.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Cantwell, Barkley & Blackburn (2010) demonstrated that sudden expansions cause the amplification of the inlet noise and Zhang & Luo (2018) demonstrated that sudden constrictions may induce an increase of the swirl intensity, which therefore promotes mixing. All these parameters should be in the scope of future studies and may eventually lead to help the design of the following: (i) sorting microsystems such as those described by Kadivar & Farrokhbin (2017), Park et al (2009), Chang et al (2010) or Volpe, Gaudiuso & Ancona (2019), which may possibly be improved by controlling the size of the recirculation zones; (ii) microreactors such as the microcrystallizer described by (Rimez et al 2019), which may also be improved by promoting passive mixing. k| Re = 400 FIGURE 10.…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidics technology refers to the precision control and manipulation of fluids at the submillimeter scale. Generally, microfluidic systems transport, separate, and mix the fluids, and this technology has been applied in deoxyribonucleic acid (DNA) chip, micropropulsion, microthermal, and lab-on-a-chip technology [ 1 , 2 , 3 ]. Generally, soft lithography technology [ 4 ] is used to define the pattern and channel on substrates, such as wafer or glass.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent materials are used in an increasing number of applications, ranging from microelectronics [1], to microfluidics [2,3] and optoelectronics [4]. In particular, glass, quartz and sapphire, due to their broad spectral band of light transmission, hardness and scratch-resistance, are good candidates for display components of portable mobile electronics, as light emitting diode (LED) substrates, protection mirrors of mobile phone cameras, smartwatches, etc.…”
Section: Introductionmentioning
confidence: 99%